Lesbian death : desire and danger between feminist and queer - Sullivan, Mairead, 1981- (University of Minnesota Press, 2022)
"In Lesbian Death, Mairead Sullivan probes the perception that lesbian status is in retreat, exploring the political promises-and failures-of lesbian feminism and its usefulness today. Sullivan reads how lesbian is conceptualized in relation to death from the 1970s onward, arguing that lesbian offers disruptive potential and offering a fresh perspective on her value for feminist and queer projects"--